Incentives in Water Management Reform: Case Study in the Yellow River Basin - Wang, Jinxia; Xu, Zhigang; Huang, Jikun; Rozelle, Scott (Water Nepal, 2004)
The paper which aims to better understand water management reform in China’s rural communities, especially focusing on the effect that improving incentives to water managers will have on the nation’s water resources and the welfare of the rural population, has three objectives. First, we track the evolution of water management reform and seek to identify the incentive mechanisms that encourage water managers to use water more efficiently. Second, we identify the impact of the incentives provided to water managers on crop water use. Then we explore how changes in incentives also affect agricultural production, farmer income and poverty status. The analysis demonstrated that it is not the nominal implementation of the reform that matters: rather, it is the creation of new management institutions that offer water managers monetary incentives which lead to water savings. Significantly, given China’s concerns about national food production and poverty alleviation, the reductions in water, at least in our sample sites, did not lead to reductions in either production or income and did not increase the incidence of poverty. Water Nepal Vol.11(2) 2004 pp.103-130